Reframing Intellectual Property Law in Sri Lanka Lessons from the Developing World and Beyond - Marsoof, Althaf; Kariyawasam, Kanchana; Talagala, Chamila (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book is a reflection on domestic intellectual property lawmaking from a developing country's perspective. It focuses on Sri Lanka-a South Asian jurisdiction with a socio-economic, cultural, and political landscape similar to other developing nations in the region, but the intellectual property regime of which has been less explored. The aim of this book is to address the discrepancies, gaps, and flaws in the national intellectual property legal framework of Sri Lanka. In doing so, the book considers Sri Lanka's obligations under TRIPS and other related intellectual property treaties to which the country is a party. The book also examines approaches adopted by developing countries in the region and beyond, as well as other more developed nations, in calibrating Sri Lanka's domestic intellectual property regime to better address the country's domestic needs and national interests. The approach adopted in this book is of relevance, more generally, to policymakers, legislators, legal academics, scholars, jurists, legal practitioners and judges who are keen on exploring the extent to which domestic intellectual property legislation complies with international intellectual property norms and standards and, more importantly, the extent to which domestic law makes use of the flexibilities under international law in addressing domestic needs and national interests.
Sri Lanka: An Introduction to a Rising Nation -- Obligations, flexibilities and domestic implementation of international intellectual property law -- Patents: Acquisition, Nature and Scope of Rights -- Plant Varieties, Plant Breeders' and Farmers' Rights -- Trade Marks: Acquisition, Nature and Scope of Rights -- Geographical Indications -- Copyright: Subject Matter, Nature and Scope of Rights.
Keywords: Information technology-Law and legislation; Mass media-Law and legislation; Private international law; Conflict of laws; International law; Comparative law; Law and economics; IT Law, Media Law, Intellectual Property; Private International Law, International and Foreign Law, Comparative Law; Law and Economics